Penetrating Orbital Sphenoid Sinus Trauma with a Wooden Stick: A Challenging Case Report - Marie-Louise Uhre Hansen; Mads Thorsberger; Jesper Skovlund Jørgensen; Christian von Buchwald (Case Reports in Ophthalmology, 2020)
Transorbital and intra-sphenoidal traumas are relatively uncommon, can be challenging to manage, and are associated with a high risk of complications and potentially fatal outcome. Transorbital and intra-sphenoidal trauma pose a medical challenge due to close relationship to delicate and critical anatomical structures, such as the globe, optic nerve, the ophthalmic internal carotid arteries, and central nervous system. Rapid admission to a level 1 trauma center with a high surgical expertise level is essential to ensure the best possible treatment and outcome. We present a case of a 75-year-old man who had a severe orbital trauma, where a wooden foreign object penetrated the orbit into the sphenoid sinus without penetrating its posterior wall. This case is important because of the rare trauma presentation with a wooden foreign object, which can easily be missed on computed tomography. The case also illustrates the importance of close collaboration between ophthalmologists and rhinologists when challenged with severe orbital sphenoid sinus trauma.